Strategies for Fiscal Consolidation in Japan - Botman, Dennis (IMF Working Papers; Working Paper, 2007)
Japan's key fiscal challenge is to put public finances on a more sustainable footing. This paper investigates the macroeconomic implications of alternative fiscal strategies for Japan using the IMF's Global Fiscal Model. The results suggest that: (i) an adjustment package that achieves primary balance through lower social transfers and government spending and a higher VAT is the most viable option and has a smaller negative impact on growth than other fiscal measures; (ii) achieving primary balance is not sufficient to stabilize the net debt ratio; (iii) prefunding future aging costs provides greater long-term benefits compared with less front-loaded strategies; (iv) tax reform involving shifting from corporate taxation to consumption taxation could mitigate the short-term output losses associated with fiscal consolidation; and (v) the spillovers to the rest of the world from consolidation in Japan are positive in the medium term, but modest.